Optimalisasi Fungsi Pelayanan Terminal Singaparna Kabupaten Tasikmalaya - Ida Farida; Rizki Saepul Ulum (Jurnal Konstruksi, 2026)
The Tasikmalaya Regency Government will rebuild the Singaparna terminal. To relocate the terminal which was originally located near Singaparna square and close to Singaparna Market will be moved to Cisinga road Padakembang Subdistrict Tasikmalaya Regency, currently Singaparna terminal is far from standard, making riders and passengers complain because of its poor facilities, such as service facilities, waiting chairs are few and damaged, bus departure schedules, and the situation around the terminal is not organized. So the purpose of this study is to identify the existing conditions of Singaparna Terminal capacity, analyze the performance of Singaparna Terminal services and Design for capacity optimization in the new Terminal. This research was conducted by taking primary data (Observation, Survey, Interview) and secondary data (Number of Tracks, Volume of public transportation, Terminal Area). In this study the method used is quantitative method and Customer Satisfaction Index (CSI) with field observations, surveys and interviews to passengers and drivers in the terminal with data processing using the SPSS program. The conclusion obtained from this study is the number of public transportation in Singaparna Terminal for 6 hours within 1 week is 1,522 vehicles. The CSI value obtained for the whole is 48.77 percent seen in table 2.1.that the level of customer satisfaction with Singaparna terminal services has quite satisfied criteria because the results of the percentage index are 40% less than Satisfaction index less than equal to 60 percent.